Discovery and development of differentially methylated regions in human papillomavirus‐related oropharyngeal squamous cell carcinoma. Issue 10 (21st September 2018) - Ren, Shuling; Gaykalova, Daria; Wang, Jennifer; Guo, Theresa; Danilova, Ludmila; Favorov, Alexander; Fertig, Elana; Bishop, Justin; Khan, Zubair; Flam, Emily; Wysocki, Piotr T.; DeJong, Peter; et al.
Abstract : Human papillomavirus (HPV)‐related oropharyngeal squamous cell carcinoma (OPSCC) exhibits a different composition of epigenetic alterations. In this study, we identified differentially methylated regions (DMRs) with potential utility in screening for HPV‐positive OPSCC. Genome wide DNA methylation was measured using methyl‐CpG binding domain protein‐enriched genome sequencing (MBD‐seq) in 50 HPV‐positive OPSCC tissues and 25 normal tissues. Fifty‐one DMRs were defined with maximal methylation specificity to cancer samples. The Cancer Genome Atlas (TCGA) methylation array data was used to evaluate the performance of the proposed candidates. Supervised hierarchical clustering of 51 DMRs found that HPV‐positive OPSCC had significantly higher DNA methylation levels compared to normal samples, and non‐HPV‐related head and neck squamous cell carcinoma (HNSCC). The methylation levels of all top 20 DNA methylation biomarkers in HPV‐positive OPSCC were significantly higher than those in normal samples. Further confirmation using quantitative methylation specific PCR (QMSP) in an independent set of 24 HPV‐related OPSCCs and 22 controls showed that 16 of the 20 candidates had significant higher methylation levels in HPV‐positive OPSCC samples compared with controls. One candidate, OR6S1, had a sensitivity of 100%, while 17 candidates (KCNA3, EMBP1, CCDC181, DPP4, ITGA4, BEND4, ELMO1, SFMBT2, C1QL3, MIR129–2, NID2, HOXB4, ZNF439, ZNF93, VSTM2B, ZNF137P and ZNF773) had specificities of 100%. The prediction accuracy of the 20 candidates rang from 56.2% to 99.8% by receiver operating characteristic analysis. We have defined 20 highly specific DMRs in HPV‐related OPSCC, which can potentially be applied to molecular‐based detection tests and improve disease management. Abstract : What's new? High‐risk human papillomavirus (HPV) infection plays an important role in the pathogenesis of oropharyngeal squamous cell carcinoma, but population‐based HPV screening similar to cervical cancer is not yet in place. To define other measurable DNA alterations apart from HPV, the authors performed genome‐wide quantitative DNA methylation profiling and identified 20 differentially methylated regions with high prediction accuracy for HPV‐positive oropharyngeal tumors, opening the door for the development of detection assays as well as defining epigenetic alterations associated with HPV‐positive tumors.